Intended and unintended impacts of the comprehensive reform of urban public hospitals: A mixed-method study in Hangzhou, China - Tao Zhang; Jing Liu; Beiyin Lu; Zhongheng Yan; Xiaojun Huang; Wei Lu; Wei Lu (Frontiers Media S.A., 2022)
ObjectivesPublic hospital reform is a key area in the Chinese healthcare system reform with the aim of controlling excessive growth of medical expenditures. This study aims to evaluate the impacts of two rounds of urban public hospital reforms respectively starting in 2018 and 2019.MethodA mixed-method method was conducted in Hangzhou. In the quantitative phase, monthly data covering 7 provincial, 12 municipal, and 35 district hospitals from March 2017 to June 2020 was analyzed using a panel-interrupted time-series. Thematic content analysis was conducted using qualitative data collected from 32 in-depth interviews.ResultsQuantitative data showed a considerable reduction in the proportion of drug revenue (provincial hospitals: −4.937%; municipal hospitals: −2.765%; district hospitals: −2.189%) and an increase in the proportion of consumable (provincial hospitals: β2 = 2.025; municipal hospitals: β3 = 0.206) and examinations (provincial hospitals: β2 = 1.354, β3=0.159; municipal hospitals: β2 = 1.179) revenue after the first reform. In post-reform 2, The respective instant decrease and increase in the proportion of consumable (provincial hospitals: −2.395%; municipal hospitals: −0.898%) and medical services (provincial hospitals: 2.115%; municipal hospitals: −2.604%) revenue were observed. Additionally, quantitative and qualitative data indicated inpatient expenditures dropped considerably after the reform. However, insufficient compensation for medical services and increased financial pressure on hospitals were repeatedly mentioned as unintended consequences in qualitative interviews.ConclusionsOverall, the urban public hospital reforms in China created positive effects in adjusting hospital revenue structure and constraining soaring medical expenditures. Unintended consequences remind policymakers to establish rational and dynamic compensation mechanisms for public hospitals.